Kajian Tingkat Penerimaan Panelis pada Dark Chocolate Bar dengan Penambahan Bubuk Kayu Manis (Cinnamomum burmannii) - Danar Praseptiangga; Yasmin Nabila; Dimas Rahadian Aji Muhammad (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Indonesia is an agricultural country that is recognized as the third-biggest of cocoa producer in the world, after Cote d’Ivoire and Ghana. Widely cultivated in Indonesia, cinnamon is potential to be developed, since it has an excessive potency as an antioxidant and flavoring agents. The panelists’ acceptance of dark chocolate bars with cinnamon powder addition based on sensory tests was evaluated in this study. A completely randomized design (CRD) with one factorial was used. Variation of addition in cinnamon powder used in this study was 10% (F1), 15% (F2) and 20% (F3). Based on the result of scoring tests on colour, aroma, taste, appearance, and overall attributes of the sensory analysis, dark chocolate bar with 10% addition of cinnamon powder was chosen as the best formula. Thus, it may conclude that the highest level of panelists’ acceptance and preferences for some of the sensory attributes evaluated in this study is the dark chocolate bar with 10% addition of cinnamon powder. However, physical and chemical characterizations of the dark chocolate bars with cinnamon powder are still needed for further evaluation to gain a more comprehensive understanding about their quality attributes.